Recombination and long-term relaxation of photoconductivity in р⁺–р–р⁻ structures of CdxHg₁₋xTe - Ismayilov, N.J.; Rajabli, A.A.; Musayev, M.A.; Abbasov, I.I. (Физика низких температур, 2018)
The paper presents the results of a study of the photoconductivity of р⁺–р–р⁻ structures of CdxHg₁₋xTe (0.24 ≤ x ≤ 0.29) single crystals obtained by thermal diffusion of copper at T = 130°C. The long-term relaxation (LR) of photoconductivity with a duration of up to 10 ms in the presence of a thermal background of intensity Φ = 10¹⁶–10¹⁷ cm⁻²⋅s⁻¹ is observed for the first time in narrow-gap materials in the T = 77–150 K range. Recombination, diffusion-drift processes in the sample are analyzed, which cause LR and spectral features of photoconductivity. The obtained structures are promising for the development of various highly sensitive IR detectors with an elevated operating temperature. Представлено результати дослідження фотопровідності р⁺–р–р⁻ структур монокристалів
CdxHg₁₋xTe (0,24 ≤ x ≤ 0,29), отриманих термічною
дифузією міді при T = 130 °C. Довгострокова
релаксація (ДР) фотопровідності з тривалістю до
10 мс при наявності теплового фону інтенсивності
Φ = 10¹⁶–10¹⁷ cm⁻²⋅s⁻¹ вперше спостерігається в
вузькощілинних матеріалах в діапазоні Т = 77–150 К.
Проаналізовано рекомбінацію, дифузійно-дрейфові
процеси в зразку, які викликають ДР та спектральні
особливості фотопровідності. Отримані структури є
перспективними для розробки різних високочутливих
ІК-детекторів з підвищеною робочою температурою.